1992
DOI: 10.1007/bf02307269
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (VI) reducing capacity of ascorbic acid and of human plasma in vitro

Abstract: In the metabolism of chromium(VI) its reduction in human plasma is of importance; an extracellular reduction of Cr(VI) is regarded as a detoxification step. Ascorbic acid has been suggested to represent the majority of the Cr(VI)-reducing capacity of human plasma. Therefore the kinetics of the reaction of Cr(VI) with ascorbic acid, at biologically realistic concentrations were studied. Ascorbic acid, in 0.2 M HEPES buffer and at concentrations ranging from 14.2 to 113.6 nmol ml-1 (2.5-20.0 microgram ml-1), was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…'2 A recent study reported that plasma reducing capabilities for chromium(VI) ranged from 25 to 33 #g/i, however, these reducing capabilities did not correlate with plasma ascorbic acid concentration. 34 There was no significant effect of chromium exposure on damage to DNA, measured as DNA strand breaks and formation of 8-OHdG, in the present study. This accords with the findings of an animal study in which a single intratracheal dose of sodium dichromate (004 mg Cr/kg), approximately corresponding to an exposure level at the MEL of 005 mg/M3 over an 8 h working day, was not found to induce increased DNA strand breaks in rat lymphocytes compared with controls.20 This is also consistent with the results of chromium concentration in lymphocytes.…”
Section: Discussioncontrasting
confidence: 64%
“…'2 A recent study reported that plasma reducing capabilities for chromium(VI) ranged from 25 to 33 #g/i, however, these reducing capabilities did not correlate with plasma ascorbic acid concentration. 34 There was no significant effect of chromium exposure on damage to DNA, measured as DNA strand breaks and formation of 8-OHdG, in the present study. This accords with the findings of an animal study in which a single intratracheal dose of sodium dichromate (004 mg Cr/kg), approximately corresponding to an exposure level at the MEL of 005 mg/M3 over an 8 h working day, was not found to induce increased DNA strand breaks in rat lymphocytes compared with controls.20 This is also consistent with the results of chromium concentration in lymphocytes.…”
Section: Discussioncontrasting
confidence: 64%
“…Under physiological conditions, Cr VI is reduced by microsome, mitochondria and by some non-enzymatic cellular components. As a cellular component, ascorbic acid is known to reduce Cr VI to Cr III in vivo [1,2] and through inner-sphere electron transfer reactions in vitro [3,4]. The final Cr III ascorbate complexes may be of considerable interest in biocoordination chemistry aiding a better understanding of chromium metabolism and also targeting miscellaneous potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, the extracellular Cr(VI) reduction is considered to represent a detoxification mechanism (Jones 1990;Suzuki and Fukuda 1990;Capellmann and Bolt 1992). Cr(VI) is subject to subsequent reduction to Cr(III) within the cell (Connett and Wetterhahn 1983).…”
Section: Introductionmentioning
confidence: 99%